“I LOVE MY SELF” : PSIKOEDUKASI MENGHARGAI DIRI SENDIRI PADA KOMUNITAS REMAJA KATOLIK TIMOTIUS - Christanti, Dessi; Tedjawidjaja, Detricia (Universitas katolik Musi Charitas, 2023)
Adolescence are characterized by the process of exploring for identity. In this process, adolescents are prone to compare themselves with others, which can lead to feelings of dissatisfaction and low self-esteem. This condition is also experienced by adolescent who are members of the Timothy Catholic Youth Community in the Waru, Sidoarjo. The purpose of this community service activity is to increase self-esteem in adolescents, enabling them to know, accept, and respect themselves better. This community service activity is divided into four stages: observation and interviews, preparation, implementation, and evaluation. The activities are conducted in the form of psychoeducation, including lectures, sharing sessions, group games, and assignments. The activities was held on November 26, 2023, for two hours. The participants showed enthusiastic responses during the activity, requiring more time than initially planned. Based on the evaluation results, providing psychoeducation about self-esteem to adolescents in the Timothy Catholic Youth Community is considered effective. It helps participants to identify their strengths and weaknesses, share their true selves with others, and provide positive affirmations to themselves.